Pengaruh medan elektromagnetik pada prestasi mesin motor bakar empat langkah dengan bahan bakar gas - Achmad Rifqi In'Amullah; Nasrul Ilminnafik (Universitas Muhammadiyah Metro, 2020)
The high level of fuel oil consumption in Indonesia caused by increases number of vehicles. Fuel oil consumption has switched into gas fuel as one of the secure alternative fuels and obtained more little gas emissions if compared with fuel oil. LPG (Liquified Petroleum Gas) is one of the alternative fuel was environmentally friendly. This research is purposed for compared performance of four-step engine with premium fuel and LPG fuel with a variety of additional electromagnetic field 600, 800, and 1000 total of copper wire windings. Using LPG fuel can increase torque generated by engine, but the result of engine power to be lower. Based on research data 800 copper wire windings can increase the number of torque and generated power compared to LPG fuel standard. LPG fuel can save fuel consumption compared to premium fuel. The most optimum decrease in fuel consumption is generated by using 1000 copper wire windings. Using LPG fuel can also reduce CO, CO2, and HC emissions levels. The best CO, CO2, and HC emissions levels are obtained from 1000 copper wire windings.Keywords: torque, power, fuel consumption, emissions, and LPG.